Application of microfluidic chip technology to study the inhibitory effect of tetramethylpyrazine on platelet aggregation, activation, and phosphatidylserine exposure mediated by pathological high shear rate. Issue 1 (10th January 2023) - Zhang, Tiancong; Liu, Ling; Huang, Xiaojing; Gao, Xuemei; Chen, Dan; Huan, Xuanrong; He, Cui; Li, Yuan
Abstract : Objective: In order to study the antithrombotic effect and mechanism of tetramethylpyrazine (TMA). Methods: In this study, we developed a microfluidic chip model that can mimic normal arteries and stenotic arterial vessels, and studied the inhibitory effects of TMA on platelet aggregation, activation (P-selectin, GPIIb/IIIa, monocyte-platelet aggregates) and phosphatidyl serine (PS) exposure. In addition, we also investigated the effect of TMA on ADP and ristocetin-induced platelet aggregation by turbidimetry. Results: The results showed that TMA significantly inhibited the platelet aggregation, activation and PS exposure induced by pathological high shear rate. Under static conditions, TMA can inhibit ADP and ristocetin-induced platelet aggregation. Conclusion: The results indicated that TMA mainly inhibited platelet aggregation, activation and PS exposure by inhibiting the binding of von Willebrand factor (vWF) to the GPIb/IX/V complex, and partially inhibited platelet aggregation through the platelet P2Y12 –ADP receptor pathway.